Politics Of Women Empowerment: A Case Study Of Benazir Bhutto Shaheed Youth Development Program (BBSYDP) In Sindh, Pakistan - Shah, Erum (2018)
Women empowerment has been one of the core policy objectives of Asian governments and Pakistan is not an isolated case. This research study investigated the link between the women empowerment policies and their implementation on the ground taking Benazir Bhutto Shaheed Youth Development Program (BBSYDP) of Sindh as a case in point. To comply with the global discourse of women empowerment and development, the Government of Pakistan has taken many policy steps to empower women in the last seven decades. Despi te of these efforts, the socio-economic and political status of women on the ground has not improved significantl y as envisioned b y the ‘stated policies’.